2018
DOI: 10.1088/1361-6463/aac562
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of graphene/p-silicon Schottky junction

Abstract: We fabricate graphene/p-Si heterojunctions and characterize their current-voltage properties in a wide temperature range. The devices exhibit Schottky diode behaviour with a modest rectification factor up to 10 2 . The Schottky parameters are estimated in the framework of the thermionic emission theory using Cheung's and Norde's methods. At room temperature, we obtain an ideality factor of about 2.5 and a Schottky barrier height of ∼ 0.18 eV, which reduces at lower temperatures. We shed light on the physical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 34 publications
(49 reference statements)
1
45
0
Order By: Relevance
“…Graphene is commonly produced by exfoliation from graphite [28,29], epitaxial growth on SiC [30] or chemical vapor deposition (CVD) [31,32]. In particular, CVD produces uniform and large-scale graphene flakes of high-quality and is compatible with the silicon technology; therefore, it has been largely exploited to realize new electronic devices such as diodes [33][34][35][36], transistors [37][38][39], field emitters [40,41], chemical-biological sensors [42,43], optoelectronic systems [44], photodetectors [45][46][47][48][49][50] and solar cells [51].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is commonly produced by exfoliation from graphite [28,29], epitaxial growth on SiC [30] or chemical vapor deposition (CVD) [31,32]. In particular, CVD produces uniform and large-scale graphene flakes of high-quality and is compatible with the silicon technology; therefore, it has been largely exploited to realize new electronic devices such as diodes [33][34][35][36], transistors [37][38][39], field emitters [40,41], chemical-biological sensors [42,43], optoelectronic systems [44], photodetectors [45][46][47][48][49][50] and solar cells [51].…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of Crowell–Sze formalism, the Richardson constant is given by A * = 4 πem * k 2 / h 3 which for n‐doped silicon is A * ≅ 112 A cm −2 K −2 . However, the experimental value of Richardson constant in the graphene–silicon Schottky junction is repeatedly reported to be much lower . The presence of an interfacial dielectric layer is considered as a possible origin for the reduced Richardson constant .…”
Section: Resultsmentioning
confidence: 98%
“…However, the experimental value of Richardson constant in the graphene–silicon Schottky junction is repeatedly reported to be much lower . The presence of an interfacial dielectric layer is considered as a possible origin for the reduced Richardson constant . Considering the momentum‐position and energy‐time uncertainty principles, Trushin has shown that the out‐of‐plane velocity of carriers in graphene ( v z ) is fundamentally related to the quasiparticle lifetime (τ) and out‐of‐plane momentum uncertainty (Δ p z ) as vz~ /(Δpzτ)~Δz/τ where Δ z stands for the layer thickness .…”
Section: Resultsmentioning
confidence: 99%
“…The value estimated for A * is 142 A cm −2 K −2 . [41,42] In this way, the effective barrier heights were evaluated and are equal to 0.96 and 0.75 eV for the dark and light cases, respectively.…”
Section: Electrical Characterization Of Multilayer-graphene/si Heteromentioning
confidence: 99%